Pembrolizumab Therapy Leading to Complete Remission for Recurrence of Pulmonary Metastases after their Resection and Radical Cystectomy following Gemcitabine and Cisplatin Therapy - Kyohei Ishida; Go Hasegawa; Takehisa Hashimoto; Yohei Ikeda; Noboru Hara; Tsutomu Nishiyama (Case Reports in Urology)
A 64-year-old man was diagnosed with invasive bladder and right lower ureteral urothelial cancer with right pelvic lymph node and lung metastases. He received four courses of gemcitabine and cisplatin therapy. He underwent lung metastasectomy and radical cystoprostatectomy, with not only primary lesions but also metastatic lesions showing a complete response. New multiple lung metastases were revealed five months after adjuvant chemotherapy. On starting pembrolizumab therapy, the metastatic lesions are notably reduced in size. He is currently receiving pembrolizumab therapy, and no recurrence has been observed for over one year.